2016
DOI: 10.1038/srep22770
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in xyloglucan catabolism by the cellulosome-producing bacterium Ruminiclostridium cellulolyticum

Abstract: Xyloglucan, a ubiquitous highly branched plant polysaccharide, was found to be rapidly degraded and metabolized by the cellulosome-producing bacterium Ruminiclostridium cellulolyticum. Our study shows that at least four cellulosomal enzymes displaying either endo- or exoxyloglucanase activities, achieve the extracellular degradation of xyloglucan into 4-glucosyl backbone xyloglucan oligosaccharides. The released oligosaccharides (composed of up to 9 monosaccharides) are subsequently imported by a highly specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 53 publications
5
73
0
1
Order By: Relevance
“…12,42 Abundance of butyrate-producing Blautia was correlated with high-carbohydrate content. In the present study, the PLPE group showed reduced levels of LPS-producing Escherichia-Shigella, 11 necrotic enteritis-related Clostridium_sensu_stricto_1, 47 conditionally pathogenic Bacteroidales_S24-7_group, 43 and intestinal mucin-degraded Akkermansia. 46 Low levels of SCFA-producing bacteria in diabetic rats are enhanced by PLPE treatment.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…12,42 Abundance of butyrate-producing Blautia was correlated with high-carbohydrate content. In the present study, the PLPE group showed reduced levels of LPS-producing Escherichia-Shigella, 11 necrotic enteritis-related Clostridium_sensu_stricto_1, 47 conditionally pathogenic Bacteroidales_S24-7_group, 43 and intestinal mucin-degraded Akkermansia. 46 Low levels of SCFA-producing bacteria in diabetic rats are enhanced by PLPE treatment.…”
Section: Discussionsupporting
confidence: 51%
“…41 Dietary polysaccharides increased the abundance in intestinal tract of Prevotella, a type of succinate-producing bacteria. 34 Other bacteria potentially able to break down polysaccharides to produce SCFAs include Ruminiclostridium-9, 43 Eubacterium_xylanophilum, 44 Anaerotruncus, 45 and Oscillibacter. 12,42 Abundance of butyrate-producing Blautia was correlated with high-carbohydrate content.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cellulosomal proteins encoded by the “ xyl-doc” cluster (14 genes more specifically oriented towards hemicellulolysis [16]) did not show any significant differences, although 8 of them were quantified in the whole dataset (S1 Dataset). The cellulosomal endoglucanase Ccel_0429, presenting higher levels in Tissue incubations, could have participated to hemicellulose deconstruction since it exerts xyloglucan depolymerization as a secondary activity [39]; however its regulation mechanisms are unknown. Finally, the other cellulosomal subunits with a known xylanase activity and statistically significant differences had lower levels in Tissue incubations (Ccel_0755 in Table 2, Ccel_0931 in Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…1F and Supplemental Fig. S1G), which may be associated with cellulose degradation (50); specific mechanisms still need to be investigated in the future. Additionally, we still found that LC also selectively increased the sulfatereducing bacteria Desulfovibrio ( Fig.…”
Section: Discussionmentioning
confidence: 99%